Menjaga warisan leluhur: Keindahan tradisi Mapeed dalam Upacara Dewa Yadnya di Desa Jagapati - Kadek Mahayanti; I Wayan Suja; Ida Bagus Putu Arnyana; I Wayan Suja (Universitas Negeri Malang, 2024)
The Mapeed tradition in Jagapati Village, an annual tradition that upholds religious values and preserves Mapeed's cultural heritage, is the subject of this qualitative research. The study was conducted in Jagapati Village, Abiansemal District, Badung Regency, Bali. The research subjects were individuals from Jagapati Village involved in the Mapeed ceremony, especially traditional leaders, priests, and women who have a role in the ceremony. Informants were selected through purposive sampling based on their role, knowledge, and involvement in the tradition. Data collection techniques used in this study were observation and interviews. Data was analyzed using descriptive-qualitative analysis methods, namely data reduction, data presentation, conclusion drawing, and verification. The Mapeed tradition in Jagapati Village is a form of respect for ancestors and God, reflecting the religious, aesthetic, and socio-cultural values of Balinese society. The preservation of this tradition requires collective awareness from all parties to keep it relevant in the modern era.